Correspondence with [Dr. Michael Browne, Bishop of Galway and Kilmacduagh] - Browne, Michael J., (R.C. Bishop of Galway and Kilmacduagh), 1895-1980; Ó Ceallaigh, Seán T. (Seán Tomás), 1882-1966 (1945)
Letters and postcards mainly concern Michael’s health and visits between him and Phyllis. One letter thanks Ó Ceallaigh for the copies of The Times he sent and mentions how the Irish papers were discreet in concealing the attitude of Cardinal Gilroy. In addition, he talks about Cardinal Glennon, Dr. McQuaid, Eisenhower’s family, Pius XII and Blessed John XXIII. He also writes of seeing de Valera and Frank Aiken at a football match.
Keywords: McQuaid, John Charles, -- 1895-1973; Aiken, Frank, -- 1898-1983; De Valera, Éamon, -- 1882-1975